SAÚDE MENTAL DOS IDOSOS E CORONAVÍRUS: FALANDO SOBRE DEPRESSÃO NO PROJETO DE EXTENSÃO PUC MAIS IDADE UNAI- BETIM - Martins, Nayara Gonçalves; Silva, Dayane Jhenifer Ribeiro; Amorim, Maria Clara Botelho Vieira; Carmo, Mariana Pereira de Souza; Souza, Hertiquiano J. D. S.; Balbi, Sabrina Oliveira Viana (Sinapse Múltipla, 2020)